The rs1527483, but not rs3212018, CD36 polymorphism associates with linoleic acid detection and obesity in Czech young adults - Plesník, Jiří; Šerý, Omar; Khan, Amira S; Bielik, Peter; Khan, Naim A (The British journal of nutrition, 2018)
Recent evidence has raised the possibility of the existence of a sixth taste modality - that is, taste for fat - which is mediated by lingual CD36 and plays a role in obesity. Consequently, the genetic polymorphism of CD36 has been shown to be associated with altered oro-sensory detection of dietary lipids. In the present study, we investigated the relationship between oro-sensory perception of linoleic acid (LA), two CD36 polymorphisms (rs1527483 and rs3212018), obesity parameters and craving habits for dietary lipids in young Czech adults. We also sequenced 5 and 6 exons of CD36 to trace out any new mutation that might be responsible for the difference in taste perception. We observed that craving for dietary lipids was correlated with anthropometric parameters (P<0·05) and LA detection threshold (P=0·033). The participants with the CC genotype of the rs1527483 polymorphism had lower BMI (P=0·011), waist circumference (P=0·005), waist:height ratio (P=0·010) and higher sensitivity for LA (P=0·037) than the participants with the CT and TT genotypes. Interestingly, we did not observe any association between the rs3212018 polymorphism and the studied parameters. Moreover, we did not observe any mutation in exons 5 and 6 of the CD36 gene in these subjects. Finally, we can state that rs1527483, but not rs3212018, is associated with high body weight in young Czech subjects.
Keywords: poměr pas/výška; Young Adult; LA linoleic acid; Male; Obesity; Genotype; mladý dospělý; Česká republika; Taste; WHR waist:hip ratio; obezita; Adult; Food Preferences; preference v jídle; dospělí; mužské pohlaví; jednonukleotidový polymorfismus; Dietary Fats; WC waist circumference; rs1527483; CD36 Antigens; chuť; Czech Republic; dietní tuky; Polymorphism, Single Nucleotide; lidé; ženské pohlaví; CD36; Humans; Body Mass Index; Linoleic Acid; antigeny CD36; Genetic polymorphism; Waist-Height Ratio; chuťová percepce; WHtR waist:height ratio; Fat taste; obvod pasu; index tělesné hmotnosti; genotyp; Taste Perception; kyselina linolová; Female; Waist Circumference